A review of the family Cymothoidae (Isopoda: Cymothooidea) infesting marine fishes from Malaysian waters, with new host and geographical records - Martin, Melissa B.; Tuah, Alia; Muhamad, Juariah H.; Bruce, Niel L. (Zootaxa, 2022)
A checklist of parasitic cymothoids from Malaysian waters is presented based on available literature and material collected from 2010 to 2020. Most of the collected specimens were recorded from waters of Terengganu, east coast of Peninsular Malaysia (facing the South China Sea), whereas literature records were included from Sarawak, along the Miri coast of northwest Borneo. The checklist comprises 19 species in ten genera, seven of which are new records from Malaysia: Anilocra nemipteri Bruce, 1987; Ceratothoa barracuda Martin, Bruce & Nowak, 2015; Ceratothoa carinata (Bianconi, 1869); Cymothoa epimerica Avdeev, 1979; Elthusa sigani Bruce, 1990; Joryma engraulidis (Barnard, 1936) and Renocila richardsonae Williams & Bunkley-Williams, 1992. Eight new host records are based on collected specimens: Anilocra nemipteri was dorsally attached on Nemipterus nemurus (Bleeker, 1857), Nemipterus nematophorus (Bleeker, 1854), Nemipterus tambuloides (Bleeker, 1853) and Nemipterus thosaporni Russell, 1991 (family Nemipteridae); Ceratothoa carinata was found in the buccal cavity of Decapterus macrosoma Bleeker, 1851 (family Carangidae); Cymothoa eremita (Brunnich, 1783) was attached in the buccal cavity of Nemipterus tambuloides (Bleeker, 1853) and Nemipterus furcosus (Valenciennes, 1830); Elthusa sigani was found attached on the gills of Pterois russelli Bennett, 1831 (family Scorpaenidae), and Renocila richardsonae was attached on the caudal fin of Upeneus japonicus (Houttuyn, 1782) (family Mullidae). All cymothoid species listed here are known to have a Central Indo-Pacific distribution, with some ranging as far as the Western Indian Ocean. A cymothoid–host association is here listed from 28 fish families, with the most commonly reported from Carangidae (pompanos, jack mackerels, runners, scads), Engraulidae (anchovies), and Leiognathidae (ponyfishes, slipmouths). This paper is the first comprehensive review of both verified literature records and deposited specimens. A key for the family of Cymothoidae in Malaysian waters is given.